1987
DOI: 10.2307/2531533
|View full text |Cite
|
Sign up to set email alerts
|

Statistical Analysis of the Michaelis-Menten Equation

Abstract: An application of the method of maximum likelihood (ML) is described for analysing the results of enzyme kinetic experiments in which the Michaelis-Menten equation is obeyed. Accurate approximate solutions to the ML equations for the parameter estimates are presented for the case in which the experimental errors are of constant relative magnitude. Formulae are derived that approximate the standard errors of these estimates. The estimators are shown to be asymptotically unbiased and the standard errors observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
89
1
2

Year Published

1990
1990
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(92 citation statements)
references
References 18 publications
0
89
1
2
Order By: Relevance
“…The rarefaction curve was based on 100 randomizations of the number of replicates sampled. We focused our investigation on five non-parametric estimators as well as on the asymptotic Michaelis-Menten (MM) richness estimator (Raaijmakers 1987) (Table 1). These six estimators were previously used in several evaluations and were reported to perform well (Walther and Moore 2005, see their table 3).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…The rarefaction curve was based on 100 randomizations of the number of replicates sampled. We focused our investigation on five non-parametric estimators as well as on the asymptotic Michaelis-Menten (MM) richness estimator (Raaijmakers 1987) (Table 1). These six estimators were previously used in several evaluations and were reported to perform well (Walther and Moore 2005, see their table 3).…”
Section: Materials and Proceduresmentioning
confidence: 99%
“…This is known as the Eadie-Hofstee equation and is recommended by Colwell and Coddington (1994) as being least likely to produce biased estimates. If Xi = S ( n )/ n and Yi = S ( n ), then Raaijmakers (1987) showed that the maximum likelihood estimate for ␤ is…”
Section: Species Richness In Same-day Versus Different-day Surveysmentioning
confidence: 99%
“…For each approach, we calculate the trajectory of the species accumulation curve and its predicted final asymptote (i.e. the total species richness), using maximum likelihood methods (Raaijmakers 1987). We also examine the dependence of species richness estimates in the different-day surveys on the temporal spacing of repeat visits.…”
Section: Introductionmentioning
confidence: 99%
“…This estimator is calculated by repetitive random sampling and fitting an asymptotic model, following the method of Raaijmakers (1987). For each sample size (from 2 to the number of observations -1), the average number of species in the sample is calculated over the random samples (the default is 100 samples for each sample size, but a higher number may be better for some data).…”
Section: Michaelis-mentenmentioning
confidence: 99%
“…This is the Michaelis-Menten equation used in enzyme kinetics and thus there is an extensive literature discussing the estimation of its parameters, which unfortunately presents considerable statistical difficulties (Colwell and Coddington, 1994). The method implemented in DIVA-GIS, favored by Raaijmakers (1987), is to calculate S max and B using their maximum likelihood estimators as follows:…”
Section: (Equation 3)mentioning
confidence: 99%